THE IMPLEMENTATION OF THE PROBLEM-BASED LEARNING (PBL) MODEL TO IMPROVE THE ACTIVENESS AND LEARNING OUTCOMES OF GRADE XI STUDENTS AT MAS ATTAQWA PUSAT PUTRI BEKASI - Ilyasa, Zuhriyah; Aripin, Syamsul (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2025)
This classroom action research aims to improve the activeness and learning outcomes of eleventh-grade students at MA Attaqwa Pusat Putri Bekasi in the subject of marriage (fikih) through the implementation of the Problem Based Learning (PBL) model. This research was motivated by the low enthusiasm and activeness of students in fikih learning, which impacted the low psychomotor and affective learning outcomes. The subjects of the research were 20 female students from class XI.2 MA Attaqwa Pusat Putri. The study was conducted in two cycles, with each cycle including planning, action implementation, observation, and reflection. Data was collected through student activeness observation sheets and learning outcome tests (pre-test and post-test). Data analysis utilized descriptive percentage techniques. The results showed an increase in student activeness across various aspects, such as listening activities (from 86% to 88%), oral activities (from 45% to 61%), and visual activities (from 35% to 78%). Furthermore, there was an increase in the average learning outcomes score from 88 in cycle I to 97 in cycle II, as well as an increase in the "very high" category from 16 to 20 students. This indicates that the PBL model is effective in enhancing student activeness and learning outcomes in fikih. Penelitian tindakan kelas ini bertujuan untuk meningkatkan keaktifan dan hasil belajar peserta didik kelas XI.2 MA Attaqwa Pusat Putri Bekasi pada materi pernikahan melalui penerapan model pembelajaran Problem Based Learning (PBL). Penelitian ini dilatarbelakangi oleh kurangnya antusiasme dan keaktifan peserta didik dalam pembelajaran fikih, yang berdampak pada rendahnya hasil belajar ranah psikomotorik dan afektif. Subjek penelitian adalah 20 peserta didik perempuan kelas XI.2 MA Attaqwa Pusat Putri. Penelitian dilaksanakan dalam dua siklus, dengan setiap siklus meliputi perencanaan, pelaksanaan tindakan, observasi, dan refleksi. Data dikumpulkan melalui lembar observasi keaktifan siswa dan tes hasil belajar (pre-test dan post-test). Analisis data menggunakan teknik deskriptif persentase. Hasil penelitian menunjukkan peningkatan keaktifan peserta didik pada berbagai aspek, seperti listening activities (dari 86% menjadi 88%), oral activities (dari 45% menjadi 61%), dan visual activities (dari 35% menjadi 78%). Selain itu, terdapat peningkatan nilai rata-rata hasil belajar dari 88 pada siklus I menjadi 97 pada siklus II, serta peningkatan kategori nilai sangat tinggi dari 16 menjadi 20 peserta didik. Hal ini menunjukkan bahwa model PBL efektif dalam meningkatkan keaktifan dan hasil belajar peserta didik pada mata pelajaran fikih.